Doktrin Akhir Zaman (Ekshatologi) - Selarista Selarista; Resna Winandar; Novan Yakhin Gamaliel; Sarmauli Sarmauli (Publisher STPKat, 2024)
End-times doctrine, or eschatology, is a part of theology that discusses events that will occur at the end of life and world history, especially from a Christian perspective. This topic covers various views on death, resurrection, final judgment, and the second coming of Christ. Eschatology in the Old and New Testaments focuses on the promise of salvation and the hope of God’s Kingdom. This research was carried out using a literature study method by collecting and analyzing various theological literature, holy books and other relevant sources to study the concept of the end times. The aim is to explore developing eschatological views, both from a historical and theological perspective. Eschatology offers deep insight into the promised future, as well as the role of the presence of Jesus Christ in human history.